Nanowire-based zinc-doped tin oxide microtubes for enhanced solar energy utilization efficiency. Issue 9 (15th June 2017) - Mao, Wutao; Li, Zhengdao; Bao, Keyan; Zhang, Kaijun; Wang, Weibo; Li, Beibei
Abstract: Nanowire-based Zn-doped SnO2 microtubes are synthesized via a solvothermal route for solar energy utilization. The unique architecture exhibits a hierarchical structure: the interconnected nanowires vertically stand on the surface of tube with several micrometers in length. With this structure as photoanodes for the dye-sensitized solar cells (DSSCs), an overall 4.22% photoconversion efficiency is obtained, which is nearly thrice as high as that of the DSSCs constructed using a photoanode of commercial SnO2 nanoparticles. Moreover, with the Zn-doped SnO2 as the photocatalyst, it exhibits both higher photocatalytic activity and better recyclability for the degradation of dyes. These improvements are ascribed to fast electron transport, high surface area, and promoted charge separation made possible by the fancy structure of Zn doping into the SnO2 framework.